IMPLIKASI PENGAKUAN PUTUSAN ARBITRASE INTERNASIONAL DALAM HUKUM INDONESIA DAN HUKUM INTERNASIONAL - Muhammad Hanif Asror; Fatma Ulfatun Najicha (Borneo Law Review, 2023)
Abstrak Penerapan klasifikasi Putusan Arbitrase Internasional menurut Undang-UndangArbitrase dan Alternatif Penyelesaian Sengketa (APS) berimplikasi terhadapkewenangan pengadilan domestik dengan meluasnya kewenangan pengadilan domestik terhadap kasus arbitrase yang memiliki unsur asing. Dalam segi pengaturan hukum internasional, arbitrase diatur dalam proses persengketaannya dalam United Nations Commission On International Trade Law: Model Law on International Commercial Arbitration 1985 with Amendments as Adopted in 2006 (UNCITRAL Model Law) dan untuk pengakuan putusan arbitrase internasional sendiri diatur dalam Konvensi New York 1958. Artikel ini akan membahas mengenai implikasi penerapan dan pengakuan putusan Arbitrase Internasional menurut hukum Indonesia terhadap kasus yang memiliki unsur internasional.Keywords: International Arbitration; Arbitral Award; Choice of Law.AbstractThe application of the classification of International Arbitration Awards according to theArbitration and Alternative Dispute Resolution (APS) Law has implications for theauthority of domestic lawsuits by adding domestic authority to arbitration cases that have foreign elements. In terms of international law arrangements, arbitration is regulated in the dispute process in the United Nations Commission On International Trade Law: Model Law on International Commercial Arbitration 1985 with Amendments as Adopted in 2006 (UNCITRAL Model Law) and for the recognition of international arbitral awards themselves are regulated in the New York Convention 1958. This article will discuss the application and recognition of International Arbitration penalties according to Indonesian law in cases that have an international element.